MATLAB Simulation on Integration of Hybrid PV-Wind-Battery based system joined with Dc-Dc Converter - Lakshmi, B.Prasanna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The proposed paper has a control approach required for power run management of the system grid-connected hybrid PV-wind-battery based system with an efficient multi-input transformer joined bidirectional dc-dc converter is presented. The main aim of my project is to convince the load demand, manage the power flow from special sources, inject surplus power into the grid and charge the battery from grid as and when required. A transformer fixsed boost up half-bridge converter is used to exploit power from wind, while two directional buck-boost converters is used to exploit power from PV along with battery charging/discharging control. A single-phase fullbridge bidirectional converter is used for feeding ac loads and communication with grid. The planned converter architecture has compressed number of power conversion stages with less component count, and reduced losses compared to offered grid-connected hybrid systems. Simulation results obtained using MATLAB/Simulink show the performance of the proposed control strategy.